(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Bonded Labour exists mainly in the Asian countries and agricultural societies. This type of labour is related to the cases where monetary or financial contracts occur such as loans, which if the debtor find himself to pay unable, he has to serve the creditor for some specific period or unspecific period. The present study highlights the analysis of the economic and working conditions of bonded labour in Ellenabad and Nathusari Chopta of Sirsa district of Haryana. Main objectives of the study are examine the economic conditions of bonded Labour, the problems and working conditions of bonded labour and find out the reach level of different schemes to the concerned working class. For this purpose primary data were collected through interview method and percentage method was used for analysis the data. Finding of the study reveals that the bonded labours are leading a very miserable life.